Towards Formative Mobile-assessment In Esp Using Bloom’s Digital Taxonomy - Belkhir, Asma (جامعة الوادي - University of Eloued, 2020)
The present study aims at bridging formative mobile assessment practices with smartphones in the ESP context to assess students’ grammar and vocabulary learning using Bloom’s digital taxonomy. The researcher opted for an experimental study both pre and posttest were designed for third-year Banking and Insurance students to compare their grammar and vocabulary learning by means of smartphones usage along with Bloom’s digital taxonomy. A mobile application has been designed as an initiative to assess grammar and vocabulary learning to serve formative assessment. Findings reveal that the experimental group performed better than those of the control group, and that Bloom’s digital taxonomy proved to be worthy for formative mobile assessment practices among ESP learners.
مقال
Keywords: Formative Mobile assessment ; Smartphones ; Bloom’s Digital Taxonomy ; ESP ; Grammar and